Emotional sociology applied: predictive influence of affective neuroscience personality traits on Chinese preschool teachers’ performance and wellbeing - Lu, Ling; Jian, Lu (Frontiers in Psychology, 2024)
Background The interplay between teaching engagement and performance has garnered attention in both theoretical and empirical research, primarily due to its influence on student academic achievement, teacher well-being, and the realization of institutional goals. This is especially pertinent in the realm of preschool education, where the scope of learning extends beyond academic content to encompass the broader socialization of children. Drawing from Affective Neuroscience research, this study investigates the role of affective tendencies as mediators in the relationship between work engagement and job performance. Objective The primary aim of this research is to examine a chain mediation model that hypothesizes the predictive role of teacher engagement. This model posits the intermediary influence of four basic emotions—CARING, SEEKING, ANGER, and FEAR—followed by the mediating effect of job satisfaction on teacher job performance. Method The study utilized a sample of 842 Chinese preschool teachers. Data were collected through an online questionnaire, employing a time-lagged design. The analysis was conducted using Model 80 of the PROCESS Macros. Results The findings reveal that both positive and negative emotions significantly predict teachers’ job satisfaction. However, job satisfaction does not influence job performance. The analysis confirmed the direct and total effects of teacher engagement, as well as the indirect effects, particularly through the positive emotion of Caring. Implications The results are instrumental in informing and refining interventions designed to enhance teacher engagement and performance, underscoring the importance of emotional factors in the educational environment.